(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article presents the features of the Standards and Guidelines for Quality Assurance in the European Higher Education Area (ESG), the alignment of the quality assurance standards of the RA with those of ESG 2015, as well as the problems of applying those standards in the higher education system of the RA. To overcome the problems presented in the article, the need to review the policies and strategies adopted at the state and institutional levels, especially the criteria and standards for quality assurance of the Republic of Armenia, is emphasized while taking into account the development taking place in the state and international educational spheres.